The comparative analysis on the laws governing national service between Malaysia, Singapore, South Korea, the United Kingdom, Sweden and Philippines / Hariz Sufi Zahari …[et al.] - Zahari, Hariz Sufi; Muhammad Ikhwan Kwan, Jasmin; Zulfakar, Mawaddah Munirah; Khairulmaini, Muayyad (2014)
The Malaysian National Service has been viewed to be lacking on certain areas. This research aims to make a comparative analysis on the adequacy of the Malaysian National Service Training Act 2003 (NSTA 2003) as compared to the laws on national service in other jurisdictions including Singapore, South Korea, the United Kingdom, Sweden and Philippines. This research involves a doctrinal approach in looking into legislations that govern national services in aforementioned countries. The legislations were examined on the issues revolving five (5) themes, namely the selection of candidates, duration for each respective programed, the status of identification of conscientious objectors, the provisions with regards to the conscripts or participants' absence without leave, and the punishments to those who fail to register to the programmers as provided in the legislations. The research found that the NSTA 2003 is lacking of specific guidelines on the selection of candidates when it is compared to other countries, apart from its age limit. In addition, the duration of the Malaysian National Service has been found to be shorter than other countries, as it is only for the duration of up until three (3) months. Also, the NSTA 2003 does not recognize conscientious objectors as it does not provide the freedom for a candidate to refuse participation in the programmed. Finally, the NSTA 2003 regards absentees to be committing an offence and therefore, provides for punishments to those found guilty, ranging from fines to community service.